A Novel Hybrid Self-Organizing Clustering Routing Algorithm. (6th September 2012) - Zhu, Peng; Jia, Fei
Abstract : This paper discusses the distributed routing algorithm of wireless self-organized network and puts forward a new type of hybrid self-organizing clustering routing protocol by combining energy sense and maximum connectedness. This routing protocol adopts a mechanism which is mainly based on cluster routing with the theory of "on demand-based plane routing discovery mechanism" becoming secondary. The routing discovery and routing maintenance algorithm are also described in this paper. As the emulation experiment result shows, there is no significant difference between the routing protocol and the demand-based routing protocol; however, when there are quite a number of nodes in the network, the performance can be greatly enhanced compared with the demand-based routing protocol. The routing protocol discussed in this paper has better extendability, lower routing overhead, and better data transmission rate; thus it can extend network lifetime and enhance the network performance.